2001
DOI: 10.1519/00124278-200108000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Single-vs. Multiple-Set Strength Training in Women

Abstract: The aim of this study was to compare the effects of singleset and multiple-set strength training in women. Twentyseven women (aged 20-40 years) with basic experience in strength training were randomly allocated to either a singleset group (n ϭ 9), a 3-set group (n ϭ 9), or a nontraining control group (n ϭ 9). Both training groups underwent a whole-body strengthening program, exercising 2 days a week for 6 weeks. Exercises included bilateral leg extension, bilateral leg curl, abdominal crunch, seated hip adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
44
0
8

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 12 publications
5
44
0
8
Order By: Relevance
“…Within this context, the resistance exercise volume debate revolves around multiple-versus single-set prescription. Many studies provide support for multiple sets of exercise (Humburg et al 2007;Kraemer et al 2000;Marx et al 2001;Schlumberger et al 2001;Munn et al 2005;McBride et al 2003;Rhea et al 2002). Conversely, some studies suggest that a single set of exercise is just as effective for increasing dynamic strength (Starkey et al 1996;Ostrowski et al 1997;Hass et al 2000;Pollock et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this context, the resistance exercise volume debate revolves around multiple-versus single-set prescription. Many studies provide support for multiple sets of exercise (Humburg et al 2007;Kraemer et al 2000;Marx et al 2001;Schlumberger et al 2001;Munn et al 2005;McBride et al 2003;Rhea et al 2002). Conversely, some studies suggest that a single set of exercise is just as effective for increasing dynamic strength (Starkey et al 1996;Ostrowski et al 1997;Hass et al 2000;Pollock et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that compared multiple-and single-set resistance training programs in trained individuals are typically between one and three or four sets (Hass et al 2000;Ostrowski et al 1997;Rhea et al 2002;Schlumberger et al 2001). Only two of these studies found benefits to multi-set prescription in trained individuals (Schlumberger et al 2001;Rhea et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated the effect of volume of resistance exercise on strength gains (Berger 1962;reviewed by Carpinellli and Otto 1998;DeHoyos et al 1998;Gotshalk et al 1997;Hass et al 2000;Kraemer et al 1995Kraemer et al ,1997Marx 1998;Sanborn et al 2000;Schulumberger et al 2001;Starkey et al 1996;Stowers et al 1983;Wescott et al 1989). The predominant recommendation has been to perform multiple sets (MS), three sets or more of a resistance exercise, rather than one single set (SS), to effectively increase one's training adaptations (Berger 1962;Gotshalk et al 1997;Kraemer et al 1995Kraemer et al , 1997Marx 1998;Sanborn et al 2000;Schulumberger et al 2001). These adaptations include increases in muscular hypertrophy, muscular strength and muscular endurance.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Starkey et al (1996) also concluded one set to failure to be as effective as three sets in increasing muscle thickness and knee extension and knee flexion isometric torque. Although almost any type of resistance training can increase strength in untrained persons, MS have been shown to produce superior strength gains over one SS to failure over a longer period of time (Berger 1962;Gotshalk et al 1997;Kraemer et al 1995Kraemer et al , 1997Sanborn et al 2000;Schulumberger et al 2001). Kraemer et al (1997) compared the effectiveness of SS versus MS on one-repetition maximum (1RM) back squat.…”
Section: Introductionmentioning
confidence: 99%